2002
DOI: 10.1002/humu.10057
|View full text |Cite
|
Sign up to set email alerts
|

Mutations ofRPGR in X-linked retinitis pigmentosa (RP3)

Abstract: Mutations in RPGR, retinitis pigmentosa GTPase regulator, are associated with RP3 type of Xlinked retinitis pigmentosa, a severe, non-syndromic form of retinal degeneration. In the majority of subjects RPGR mutations are associated with a typical rod-cone degeneration, but in a small number, cone-rod dystrophy, deafness, and abnormalities in respiratory cilia have been noted. Alternative splicing of RPGR is complex in all species examined. In RP3 patients, mutations have been found in exons 1 14 and ORF15, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 77 publications
1
49
0
Order By: Relevance
“…Altogether, the frequency of RPGR and RP2 mutations in French XLRP families is in accordance with that reported in other studies (RP2: 15.9% vs. 6-20% [Schwahn et al, 1998;Hardcastle et al, 1999;Mears et al, 1999;Thiselton et al, 2000;Miano et al, 2001;Breuer et al, 2002;Sharon et al, 2003]; RPGR: 78.4% vs. 55-90% [Roepman et al, 1996;Meindl et al, 1996;Zito et al, 1999;Vervoort et al, 2000;Buraczynska et al, 1997;Vervoort and Wright 2002;Demirci et al, 2002;Breuer et al, 2002;Sharon et al, 2003]). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Altogether, the frequency of RPGR and RP2 mutations in French XLRP families is in accordance with that reported in other studies (RP2: 15.9% vs. 6-20% [Schwahn et al, 1998;Hardcastle et al, 1999;Mears et al, 1999;Thiselton et al, 2000;Miano et al, 2001;Breuer et al, 2002;Sharon et al, 2003]; RPGR: 78.4% vs. 55-90% [Roepman et al, 1996;Meindl et al, 1996;Zito et al, 1999;Vervoort et al, 2000;Buraczynska et al, 1997;Vervoort and Wright 2002;Demirci et al, 2002;Breuer et al, 2002;Sharon et al, 2003]). …”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have reported mutations in XLRP genes [Schwahn et al, 1998;Hardcastle et al, 1999;Mears et al, 1999;Thiselton et al, 2000;Miano et al, 1999Miano et al, , 2001Breuer et al, 2002;Sharon et al, 2000Roepman et al, 1996Meindl et al, 1996;Vervoort et al, 2000;Zito et al, 1999;Buraczynska et al, 1997;Vervoort and Wright 2002;Demirci et al, 2002]. These mutations have recently been referenced in the Human Gene Database.…”
Section: Discussionmentioning
confidence: 99%
“…1 RPGR mutations also cause XL retinitis pigmentosa (RP3) and XL atrophic macular degeneration. 2,3 One of our XL CRD families demonstrated 1-nucleotide insertion mutation in exon ORF15 (1564_1565insA; seems to be the most 3= end point mutation published to date). 1 We evaluated the retinal histopathology of an affected 69-yearold family member who had been diagnosed in his 40s based on the following findings in both eyes: decreased VA (20/25), macular depigmentation and granular fine pigment deposits with absent foveal reflex, relative constriction of central VF with full peripheral fields, color vision abnormalities, slightly above normal dark adaptation thresholds, and reduction of cone and rod ERG responses (cone Ͼ rod).…”
Section: -Linked (Xl) Cone-rod Dystrophy (Crd) Is a Rarementioning
confidence: 94%
“…1 RPGR exon ORF15 mutations also cause CORDX1 (formerly COD1) type X-linked cone-rod dystrophy (CRD) and atrophic macular degeneration. 2,3 During our RPGR mutation screening of male patients with X-linked or isolated forms of RP or CRD, we identified a novel mutation (213GϾA) that was predicted to cause a nonconservative amino acid change (G52R) in RPGR protein in a patient with isolated RP.…”
Section: Utations In the Rpgr (Retinitis Pigmentosamentioning
confidence: 99%
“…A different base change at the same nucleotide position (213GϾT) has been reported and predicted to act as a nonsense mutation (G52X). 1,4,5 An alternative possibility for the major effect of this variant may be disruption of normal splicing, rather than premature termination of protein synthesis. Other presumed missense mutations may also be related to splicing if they disrupt exonic cis-splicing elements (splice sites, enhancers, silencers).…”
Section: Utations In the Rpgr (Retinitis Pigmentosamentioning
confidence: 99%